Educação jurídica indígena: superando a dicotomia pluralismo versus monismo - ALBUQUERQUE FILHO, Armando do Lago (Universidade Federal do Pará, 2019)
The curriculum structure of legal education has been built from a monistic approach, opposing the pluralistic perspective of law. This research promotes a theoretical effort to overcome the dichotomy between the two theories, aiming to contribute with the initial elements and values for the development of an indigenous legal education founded both in the monism and in the pluralism as well. In order to fulfill this goal we used the deductive method and literature review to analyze the meanings of law from the state as opposed to the legal pluralism. It determined itself the categories of general analysis to perform the duties of a position in an application of the specific native legal education.